Effects of Side Ratio on Wind-Induced Pressure Distribution on Rectangular Buildings. (12th August 2013) - Amin, J. A.; Ahuja, A. K.
Abstract : This paper presents the results of wind tunnel studies on 1 : 300 scaled-down models of rectangular buildings having the same plan area and height but different side ratios ranging from 0.25 to 4. Fluctuating values of wind pressures are measured at pressure points on all surfaces of models and mean, maximum, minimum, and r.m.s. values of pressure coefficients are evaluated. Effectiveness of the side ratios of models in changing the surface pressure distribution is assessed at wind incidence angle of 0° to 90° at an interval of 15°. Side ratio of models has considerable effects on the magnitude and distribution of wind pressure on leeward and sidewalls but it has very limited effect on windward walls at wind incidence angle of 0°. For building models with constant cross section, change in side ratio does not significantly affect the general magnitude of peak pressures and peak suctions, but rather the wind angle at which they occur. The regression equation is also proposed to predict the mean pressure coefficient on leeward wall and side wall of rectangular models having different side ratios at 0° wind incidence angle.